Metapsicologia della nevrosi ossessiva: meccanismi eziologici e patologici partendo dal caso dell’uomo dei topi - Meroni, Edoardo (Metapsychologica - rivista di psicanalisi freudiana, 2022)
The importance of metapsychological theory is emphasized both for the purpose of an etiological understanding of psychoneurosis and for an articulated explanation of character and symptomatic manifestations. Oriented mainly on the theoretical problems prompted by obsessive neurosis, an attempt will be made to highlight those invariants that are, in some cases, typical of the aforementioned neurosis, in others, generally present in every psychoneurotic affection. The case of «obsession neurosis» treated in 1907 and 1908 by Sigmund Freud in a case known as Rat Man will be the subject of our theoretical reflections. This will focus particularly on examining the most significant features of the disposition to obsessive neurosis; on the weight of fixation in psychosexual development; on what constitutes the relationship between hate and love in neurotic affections; on how ambivalence is determined in object relations; on the effects of the removal of hate; on the influences of drive events in the formation of character traits; on what constitutes the relationship between symptom and removal and on what kind of relationship exists between destruction and knowledge.